Veillonellae: Beyond Bridging Species in Oral Biofilm Ecology - Zhou, Peng; Manoil, Daniel; Belibasakis, Georgios N.; Kotsakis, Georgios A. (Frontiers in Oral Health, 2021)
The genus Veillonella comprises 16 characterized species, among which eight are commonly found in the human oral cavity. The high abundance of Veillonella species in the microbiome of both supra- and sub-gingival biofilms, and their interdependent relationship with a multitude of other bacterial species, suggest veillonellae to play an important role in oral biofilm ecology. Development of oral biofilms relies on an incremental coaggregation process between early, bridging and later bacterial colonizers, ultimately forming multispecies communities. As early colonizer and bridging species, veillonellae are critical in guiding the development of multispecies communities in the human oral microenvironment. Their ability to establish mutualistic relationships with other members of the oral microbiome has emerged as a crucial factor that may contribute to health equilibrium. Here, we review the general characteristics, taxonomy, physiology, genomic and genetics of veillonellae, as well as their bridging role in the development of oral biofilms. We further discuss the role of Veillonella spp. as potential “accessory pathogens” in the human oral cavity, capable of supporting colonization by other, more pathogenic species. The relationship between Veillonella spp. and dental caries, periodontitis, and peri-implantitis is also recapitulated in this review. We finally highlight areas of future research required to better understand the intergeneric signaling employed by veillonellae during their bridging activities and interspecies mutualism. With the recent discoveries of large species and strain-specific variation within the genus in biological and virulence characteristics, the study of Veillonella as an example of highly adaptive microorganisms that indirectly participates in dysbiosis holds great promise for broadening our understanding of polymicrobial disease pathogenesis.